The evolution and the function of Hantu in the age of pandemic COVID-19 and the media - Nur Azmina Mohd Zamani,; Ahmad Muhyiddin Yusof,; Naizrul Mubin Mohd Noor,; Mohd Muzhafar Idrus,
This paper offers a new perspective in the usage and shift of the function as well as the identity of Hantu(s) in assisting the nation to overcome the spread of Coronavirus disease (COVID19). An eclectic framework as a result of the combination between the Gothic trope and the concept of appropriation was utilised for the purpose of data analysis in this study whereby the first concept provides this study with a theme or device known as Gothic tropes that are associated with supernatural figures. The second concept, appropriation is used to understand the existence of subject's appearance and they are utilised out of their primordial context. From the analysis conducted, the findings suggest that the function of Hantu(s) has to some extent managed to assist the Indonesian government in decreasing the amount of Covid-19 spread due to its’ function in reminding the society pertaining to lethal effect of the pandemic. This is resulting from the figures of Hantu(s) and Hantu Pochong being perceived as the manifestation of the global pandemic itself. Last but not least, it was also found that the Supernatural figures or beings still gravitate fear among people in the Asian countries including today’s generation even though both Hantu(s) and Covid-19 disease are equally virulent towards the society.